The Analysis of Students’ Collocation Problems in Translations Made by English Department Universitas Negeri Padang - Rizal, Muhamat; Ardi, Havid (Journal of English Language Teaching, 2025)
This study investigates the collocational errors made by English Department students at Universitas Negeri Padang in their Indonesian–English translations. Collocational competence is essential for producing natural and fluent language, especially in EFL contexts. Using a corpus-based method and descriptive quantitative design, 21 student translations were analyzed for lexical and grammatical collocation errors using AntConc, COCA, BNC, OZDIC, and the Oxford Collocations Dictionary. A total of 45 errors were identified: 22 lexical and 23 grammatical. The most frequent error type was verb + preposition, suggesting significant L1 interference and insufficient collocational instruction. Pedagogical implications include the need for explicit teaching of collocations, integration of corpus tools, and contrastive analysis between English and Indonesian. The findings support the integration of collocational awareness into translation pedagogy for improved learner fluency and accuracy.